PENGARUH GAYA KEPEMIMPINAN BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION BERDASARKAN PERSEPSI KARYAWAN PT. ALLESIA INTERNATIONAL - Nainggolan, Hermin; Patimah, Siti; Putri, Dinar Afidah Pravita (UNIKA Santo Thomas, 2024)
This research aims to determine the influence of leadership style, workload and compensation on turnover intention at PT. Allesia International Balikpapan. The sample used in this research was employees of PT. Allesia International Balikpapan with a total of 37 respondents. The data analysis technique uses multiple regression methods assisted by the SPSS 25 program. The results of the research show that partially the leadership style variable tcount 2.651 > ttable 2.03552 with a negative direction (left) and a significance value (0.012) <0.05 has a negative effect and significant to turnover intention. The workload variable partially has a positive and significant effect on tcount 2.775 > ttable 2.03552 and a significance value of 0.009 < 0.05. The compensation variable partially has a negative and significant effect on turnover intention with a tcount of 4.433 > ttable 2.03552 and a significance value of 0.000 < 0.05. Simultaneously, it shows that the variables of leadership style, workload and compensation have a significant effect on employee performance. Based on the value obtained (F-Test), it is known that Fcount is 9.350 > Ftable 2.89 and the significance value is 0.000 <0.05.